Empowering junior high school dance education: a multimedia literacy-based competency approach for prospective teachers - Beben Barnas; Juju Masunah; Tati Narawati; Cepi Riyana (Institut Seni Indonesia Surakarta, 2025)
This study develops interactive thematic dance teaching materials integrating multimedia literacy through a competency-based approach, addressing theoretical gaps in technology integration within arts education. The research adapts Majumdar's multimedia literacy model into a six-stage pedagogical framework for kinesthetic learning, empirically validating pre-service teachers' capacity as content creators. Using Research and Development with the Thiagarajan 4D model, 27 pre-service teachers designed interactive materials validated by three experts and field-tested with 30 junior high school students. Expert validation rated materials as